Wave Energy Conversion: Overview and Control of a Permanent Magnet Linear Generator - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2019)
Renewable energies are growing fastly worldwide, especially solar and wind generation. However, the diversification of power sources is key to have more stable and resilient power systems. Marine energy has one of the highest potentials and most of the world population is near the sea. Wave energy is one of the most promising forms of marine energy, which is achieving commercial viability with bigger projects and more mature designs. However, the environment hostility and difficult access are still one of the main limitations of this technology. This paper presents the state-of-the-art of wave energy conversion (WEC), the power to take off (PTO) devices, and the specific challenges of the converters and generator drives. Finally, a field oriented control (FOC) with maximum power point tracking (MPPT) is proposed for a linear permanent magnet synchronous generator (PMSG). The simulation results show the proper control and the specific characteristics of these types of generation. © 2019 IEEE.